Membangun Pemahaman Konsep Matematis melalui Pendekatan Matematika Realistik: Systematic Literature Review - Ria Setiani Habbinnur Rizki; Ida Nuraida; T. Tutut Widiastuti (Jurnal Perspektif, 2025)
The purpose of this study was to determine whether or not there was an influence of the realistic mathematics approach on students' ability to understand mathematical concepts. This study used a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Research articles were found from the publication years 2015–2022, and they were indexed by Google Scholar. Grouping, data analysis, and drawing conclusions were the analysis techniques used. After that, the results were as follows: there was an influence of the realistic mathematics approach on students' ability to understand mathematical concepts; the presence or absence of technology in the application of the realistic mathematics approach can both improve students' ability to understand mathematical concepts; and many studies on the influence of the realistic mathematics approach on students' ability to understand mathematical concepts can be evaluated by considering the year of publication, level of education, sample size of the experimental class, status of assistance and combination of learning.